Water soluble biocompatible vesicles based on polysaccharides and oligosaccharides inclusion complexes for carotenoid delivery. (5th September 2015) - Polyakov, Nikolay E.; Kispert, Lowell D.
Graphical abstract: Highlights: Inclusion complexes of carotenoids were characterized by NMR, EPR and optical techniques. Noncovalent binding with arabinogalactan and glycyrrhizin enhances water solubility and oxidation stability of carotenoids. Noncovalent binding with glycyrrhizin increases antioxidant activity of selected carotenoids. Inclusion complexes with arabinogalactan exhibit enhanced photostability of carotenoids. Formation of inclusion complexes prevents aggregation of xanthophyll carotenoids in aqueous solutions. Abstract: Since carotenoids are highly hydrophobic, air- and light-sensitive hydrocarbon compounds, developing methods for increasing their bioavailability and stability towards irradiation and reactive oxygen species is an important goal. Application of inclusion complexes of "host-guest" type with polysaccharides and oligosaccharides such as arabinogalactan, cyclodextrins and glycyrrhizin minimizes the disadvantages of carotenoids when these compounds are used in food processing (colors and antioxidant capacity) as well as for production of therapeutic formulations. Cyclodextrin complexes which have been used demonstrated enhanced storage stability but suffered from poor solubility. Polysaccharide and oligosaccharide based inclusion complexes play an important role in pharmacology by providing increased solubility and stability of lipophilic drugs. In addition they are used as drug delivery systems to increase absorption rate and bioavailability of the drugs. In this review we summarize the existing data on preparation methods, analysis, and chemical reactivity of carotenoids in inclusion complexes with cyclodextrin, arabinogalactan and glycyrrhizin. It was demonstrated that incorporation of carotenoids into the "host" macromolecule results in significant changes in their physical and chemical properties. In particular, polysaccharide complexes show enhanced photostability of carotenoids in water solutions. A significant decrease in the reactivity towards metal ions and reactive oxygen species in solution was also detected.